Psychological Features of Verbal Communication of Employees of Preschool Education With Children From The Families of Participants of Anti-Terroristic Operations And Internally Transferred Persons - Iryna Lutsenko (Психолінгвістика, 2018)
The article is devoted to the problem of verbal communication of educators with children of preschool age from the families of participants of anti-terroristic operations (ATO) and internally displaced people. The results of theoretical analysis of the problem of studying discourse as a psycholinguistic category are presented which, in the context of vocational-speaking activity, is considered as its verbalized, foreign-language phase. The interest of psycholinguistics in the study of the peculiarities of the discourse of the educational branch – pedagogical discourse is grounded since the latter is aimed at the realization of a wide range of functions (educational, communicative organizational, psychological (psychotherapeutic)), the basis of which is the implementation of the speech-impacting teacher by the addressee on their addressees (pupils). At the same time, discourse is highlighted as a dialogical process and reveals the two-sided nature of the influence of communicators on each other. Consideration of the teacher as the subject of the speech of the individual characteristics of the child-recipient, his mental condition is considered as a prerequisite for ensuring the intentional orientation of discourse. The emphasis is placed on the implementation of psychological (psychotherapeutic) functions by educators of preschool education, which is confirmed by the needs of the practice of education and development, verbal communication with children from the families of the participants of the ATO and the internally transferred people. The types of discourses aimed at providing emotional support to children of these categories in the form of discourses-positive partial assessments are defined and characterized, namely: discourse-agreement, discourse-encouragement, discourse-approval, discourse-forward-looking positive assessment, as well as various kinds of discourse-questions. It is concluded that various discourses, in the course of which the speech influence on the child is carried out, its psychic state, feeling and behavior can be regarded as specialized discourse practice - a psycholinguistic phenomenon, the basis of which is the speech activity of its participants: educators of preschool education and children of preschool age.